Expectations of safety: realising ergonomics and safety in product design - Norris, Beverley (1998)
This research considers the role of ergonomics in consumer safety. The aim was to encourage and improve the input of ergonomics, and thus safety, into the design process. The research has resulted in a series of publications targeted specifically at designers and producers of consumer goods, with the aim of encouraging their adoption of ergonomics principles, data and methods. These publications have been produced and distributed to industry by the Department of Trade and Industry (DTI) Consumer Safety Unit: CHILDATA: The Handbook of Child Measurement and Capabilties - Data for Design Safety Designing Safety into Products: Making ergonomics evaluation a part of the design process (presented as an appendix to this thesis).